Dualism of Legal Authority in Filing Suspension of Debt Payment Obligations Petitions Against Insurance Companies (Study Case: Decision No. 389/Pdt.Sus-PKPU/2020/PN Niaga.Jkt.Pst) - Tedrick Soetedjo; Rasji (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
This article critically examines the dualism of authority in initiating bankruptcy proceedings against insurance companies in Indonesia. On the one hand, Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations and Law No. 21 of 2011 on the Financial Services Authority strictly confine such authority to the Financial Services Authority. On the other hand, in practice, Financial Services Authority’s non-response to Policyholder requests has led to interpretations invoking the doctrine of fictitious positive decisions under Law No. 30 of 2014 on Government Administration. Through normative-juridical analysis and doctrinal interpretation of the case 389/Pdt.Sus-PKPU/2020/PN Niaga.Jkt.Pst, the findings reaffirm that although fictitious decisions aim to protect citizens’ procedural rights, they cannot override the lex specialis framework of financial regulation. However, administrative silence by Financial Services Authority may still constitute an unlawful act done by the government (onrechtmatige overheidsdaad), opening paths for administrative litigation via the State Administrative Court. This paper argues for institutional reform and the reconciliation of legal objectives to effectively address administrative inaction, without compromising financial stability under the Bankruptcy and Suspension of Debt Payment Obligations regime.